2013
DOI: 10.1210/en.2012-1534
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 4 Activation Reduces Adrenal Chromaffin Cell Excitability Through a Nuclear Factor-κB-Dependent Pathway

Abstract: The adrenal medulla contains fenestrated capillaries that allow catecholamines and neuropeptides secreted by adrenal chromaffin cells (ACCs) to readily access the circulation. These capillaries may also allow bacterial products to enter the adrenal medulla and interact with ACCs during infection. One potential mediator of this interaction is toll-like receptor 4 (TLR-4), a pattern-recognition receptor that detects lipopolysaccharide (LPS) from Gram-negative bacteria. Evidence suggests that excitable cells can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 71 publications
1
10
0
Order By: Relevance
“…We therefore examined the contribution of each of these processes to the sepsis-induced changes in ACC function. Similar to previous reports (35,39), control ACCs exhibited large input resistances and fired APs in response to small current injections. Endotoxemia had no effect on resting membrane potential, input resistance, rheobase, the number of APs fired at 2ϫ rheobase, AP amplitude, AP half-width, the proportion of ACCs exhibiting spontaneous APs or the proportion of ACCs exhibiting anodal break APs (Table 1).…”
Section: Endotoxemia Enhanced Ca 2؉ -Induced Ca 2؉ Release In Accssupporting
confidence: 88%
See 2 more Smart Citations
“…We therefore examined the contribution of each of these processes to the sepsis-induced changes in ACC function. Similar to previous reports (35,39), control ACCs exhibited large input resistances and fired APs in response to small current injections. Endotoxemia had no effect on resting membrane potential, input resistance, rheobase, the number of APs fired at 2ϫ rheobase, AP amplitude, AP half-width, the proportion of ACCs exhibiting spontaneous APs or the proportion of ACCs exhibiting anodal break APs (Table 1).…”
Section: Endotoxemia Enhanced Ca 2؉ -Induced Ca 2؉ Release In Accssupporting
confidence: 88%
“…ACCs were then stimulated for 5 minutes with a 20-mM K ϩ solution, prepared by equimolar substitution of KCl for NaCl, and the supernatant was collected. In previous studies, 20 mM high-K ϩ elicited an approximately 20-mV depolarization in the ACC membrane potential, which was sufficient to elevate [Ca 2ϩ ] i and promote catecholamine secretion (35,39). As a result, high-K ϩ was the primary stimulus used to characterize the changes in ACC function during sepsis in the present study.…”
Section: In Vitro Epinephrine Release Assaymentioning
confidence: 59%
See 1 more Smart Citation
“…It is possible that LPS-mediated attenuation of anti-inflammatory status may consequently affect CA production. Furthermore, Lukewich et al (2013) reported a decreased CA response in adrenal medulla after LPS administration, where LPS via tolllike receptors (TLR-4) activation and nuclear factor kappa B-dependent pathway reduced adrenal chromaffin cell excitability. However, increased NE turnover following LPS treatment reduced the pro-inflammatory while enhanced the anti-inflammatory response (Elenkov et al, 1995;Suberville et al, 1996), indicating a physiological mechanism to limit the magnitude of an inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of the sympathetic-immune network, LPS has been shown to directly activate DRG and vagal afferent neurons [33;66]. Chronic exposure to LPS also reduces ACC excitability and inhibits neuropeptide Y release through the activation of nuclear factor (NF)-κB [67]. …”
Section: Detection Of Infection and Inflammation By The Nervous Systemmentioning
confidence: 99%